REWORK COST ANALYSIS ON COLUMN WORK IMPLEMENTATION METHODS â€œCASE STUDY: CONSTRUCTION PROJECT OF HOSPITAL ROEMANI MUHAMMADIYAH PARKING BUILDING SEMARANGâ€ - Suep, Muhamad; Husodo, Ibnu Toto; Suwandi, Putri Anggi Permata; Kristiawan, Agung (Science and Technology Research Centre, Universitas PGRI Semarang, 2022)
The word of construction is no stranger to rework. In the course of the implementation of construction, rework work may occur which can cause delays in the work process and swelling of the project cost budget. This can be influenced by several problems or factors that are often encountered during development work such as human resourse factors, documentation and disign, managerial with this can be from sevaral that have been mentioned that must be considered when planning construction development. In this study using descriptive research that directly takes data in the field by means of interviews, documentation, observation in order to be able to answer the research objectives properly and correctly according to the data obtained from the aforementioned data collection process. So that it can be seen the most frequently encountered rework jobs in the field. Based on the results of the study, it was shown that the dominant factor causing rework was managerial factor. The type of work that often experiences rework work is the finishing work of the second floor column casting. With the details of the causes of rework, the results obtained are design and documentation 22.5%, managerial 40.4%, and human resources 37.2%. The process of rework in the construction of the R S Roemani Semarang building can be concluded that there are several problems or identification of rework, namely porous columns, column slopes and column centring.